Alkaline membrane fuel cells with in-situ cross-linked ionomers. (10th January 2015) - Leng, Yongjun; Wang, Lizhu; Hickner, Michael A.; Wang, Chao-Yang
Highlights: An in-situ cross-linking strategy was adopted to prepare durable ionomers. AMFCs with in-situ cross-linked ionomers showed promising operational stability. An optimized electrode binder and electrode fabrication procedure greatly enhanced the durability performance of AMFCs. Operating AMFCs under a cathode over-humidification condition can extend lifetime. ABSTRACT: Improving cell performance and durability through both new materials and membrane electrode processing optimization is needed for the commercialization of alkaline membrane fuel cell (AMFC) technologies. In this work, we adopted an in-situ cross-linking strategy of an anion-conducting block copolymer to prepare durable ionomers for use in alkaline membrane fuel cells (AMFCs). Our goal was to use new ionomers and binders with an aim at improving long-term stability of AMFCs, especially at high operation temperatures. At 80 °C, AMFCs with in-situ cross-linked ionomers showed promising stability with an operating life time of more than 350 hours at 100 mA/cm 2 . We found that the optimized electrode fabrication process and operating conditions can significantly improve the durability performance of AMFCs. For example, a suitable electrode binder in addition to the ion-conducting ionomer can greatly enhance the durability performance of AMFCs. Operating fuel cells under a cathode over-humification condition can also enhance the long-term stability of AMFCs.